Investigation of biofilms contribution to chloramine decay in pilot scale system - Aryal Adhikari, Rekha (Curtin University, 2011)
Chloramine is often used when challenging conditions such as hot climate and long distribution systems, due to better stability and lower regulated disinfection by-products production. However, its decay can be accelerated by microbes in bulk water and on walls, referred to as biofilms. The thesis for the first time evaluated various factors (including age, nitrifying conditions and temperature) that could influence the growth of biofilms and thus its impact on chloramine decay.